2020
DOI: 10.15332/22563067.5547
|View full text |Cite
|
Sign up to set email alerts
|

Prácticas de consumo alimentario de familias desplazadas por el conflicto armado, asentadas en Bosa, Bogotá

Abstract: Colombia es el país con mayor número de desplazados internos a nivel mundial. La mayoría de las victimas provienen de zonas rurales. Este estudio tuvo como objetivo indagar y describir las prácticas de consumo alimentario actuales y previas al desplazamiento forzado. Por medio de una metodología cualitativa se analizó y teorizó el discurso de cinco mujeres víctimas de desplazamiento forzado asentadas con sus familias en la localidad de Bosa, Bogotá. Por medio de una entrevista semiestructurada se recolectó la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the case of Colombia, there are also historical, social, and geographical factors to consider. This includes forced displacement, which caused obstacles for families to obtain food, a longing for some foods and preparations usually consumed (Ruiz Pascua, 2015), as well as an increase in the consumption of calorie-dense foods such as flour, panela water (type of sugar), tubers, soups, and sausages (Puentes & Bejarano, 2020). In Girón, Santander, a study reported that the forcibly displaced families ate twice as much corn flour and a third additional of rice and panela (Prada Gómez et al, 2008).…”
Section: Potential Factors Involvedmentioning
confidence: 99%
“…In the case of Colombia, there are also historical, social, and geographical factors to consider. This includes forced displacement, which caused obstacles for families to obtain food, a longing for some foods and preparations usually consumed (Ruiz Pascua, 2015), as well as an increase in the consumption of calorie-dense foods such as flour, panela water (type of sugar), tubers, soups, and sausages (Puentes & Bejarano, 2020). In Girón, Santander, a study reported that the forcibly displaced families ate twice as much corn flour and a third additional of rice and panela (Prada Gómez et al, 2008).…”
Section: Potential Factors Involvedmentioning
confidence: 99%